INDONESIA : CLOSE SOCIETY DAN OPEN SOCIETY Perspektif Sosio-Histories tentang Dinamika Pola Sosial Kultural Fase Prasejarah, Hinduisme/ Budhisme, Islamisme dan Kolonialisme - Ashari, Ashari (Jurnal Sains Riset, 2025)
Indonesian society is the result of the construction of plural cumulative cultural patterns, which are formed from each phase of cultural dynamics from close society to open society.  The study uses qualitative methods, by comparing data from references related to library research. The results show that :  close society is intended as a cultural phase, during prehistory, as a basis for civilization. While the cultural dynamics of open society, is a phase of civilization, which is open, which is when the archipelago has experienced influences since Hinduism / Buddhism, with large kingdoms such as Majapahit and Sriwijaya, Islamism with coastal kingdoms:  Samudera Pasai Demak, Ternate, Banjar, Gowa, - and a number of other coastal kingdoms. While the phase of colonialism marked by the entry of imperialism, in the 16th century - until the 20th century, established its imperialism and colonialism. These phases show the cumulation of the heterogeneous cultural patterns that exist in Indonesia.                                   Keyword :  Indonesia, Close Society, Open Society